Analysis of groundwater pollution in a petroleum refinery energy contributed in rock mechanics through ANFIS‐AHP. (14th September 2022) - Tan, Yi; Al‐Huqail, Arwa Abdulkreem; Chen, Qiusong; Sh. Majdi, Hasan; Algethami, Jari S.; Ali, Haitham Elhosiny
Summary: Urban groundwater pollution caused by the oil industry and gas stations is a significant global environmental problem. Due to the increased demand for petroleum and petrochemical production in recent years, it is crucial to monitor and investigate the quality and contamination level of groundwater for groundwater extraction, usage, and protection. On the basis of the rock mechanic state and the features of petroleum hydrocarbon pollution in groundwater, the control parameters of petroleum hydrocarbon pollution in groundwater are investigated. Ten water samples were gathered from the vicinity of two refinery sites and experimented via a soft computing model of the adaptive neuro‐fuzzy inference system, later evaluated by the hierarchical ladder method of the analytic hierarchy process. According to the data, high and very severe pollution sites account for 31.45% of shallow phreatic water and only 20% of deep confined water, indicating that shallow groundwater is more severely contaminated than deep groundwater. Total dissolved solids, total hardness, Cl −, SO 4 2 −, and so on, which are influenced by both the natural environment and human activities, are the primary factors impacting the quality of groundwater in those regions. The primary pollutants in groundwater are nitrite and nitrate nitrogen, both of which are caused by human activities.